Determination of Economic Growth In Java Island - Ita Dwi Febrianti; Sugianto Sugianto; Renea Shinta Aminda (Ridwan Institute, 2021)
High economic growth and continuing to grow and sustainably become a component that determines the development of economic development. The level of economic growth is inseparable from the use of production factors such as natural resources, labor, and capital goods as determinants of economic growth. This research is motivated by the fact that the GRDP in Java Island has a high value compared to other islands in Indonesia. This study aims to analyze the determination of economic growth in Java. The variables used in this study are GRDP at constant prices, investment realization, open unemployment rate, and inflation rate. This study uses multiple linear regression, with a panel model which is a combination of time series data for 6 years from 2014-2019 as well as cross section data for 6 provinces in Java and using the selected Fixed Effect Model (FEM), the data is processed using the program EViews-10. The findings in this study prove that the investment variable has a positive effect on economic growth. While the unemployment variable has a negative effect on economic growth, and the inflation variable has a negative effect on economic growth.